Analisis Pengaruh Produktivitas Usaha Mikro Kecil Menengah Batik Di Kota Semarang - Lisda Rahmasari (AKUNTANSI 45, 2023)
This research is motivated by the rapid growth of small and medium micro enterprises, but it is not offset by a significant increase in productivity. By looking at existing problems, this research is aimed at analyzing the influence of factors of education, experience, capital, labor and innovation on the productivity of small micro medium in Semarang and can help the owners of medium-sized businesses improve the factors that affect productivity positively. Data collected through questionnaires and conducted on 67 businessmen Micro SME Batik Semarang City. Analysis of the data in this study using SPSS version 19. In this study population used is the Small and Medium Enterprises in the field of Fashion and Crafts batik in the city of Semarang. Population from this study gained from annuall report Disperindag Semarang in 2013. The number of samples is determined based on the calculation of the Slovin formula with a tolerable error rate of 10%, then the number of samples obtained by 67 people from 200 people in population. Data analysis method used in this research is multiple linear regression. Results of testing the hypothesis states that education is positive and significant effect on productivity, experience positive and significant impact on productivity, capital positive and significant impact on productivity, employment and significant positive effect on productivity and innovation and significant positive effect on productivity. Suggestions author to the government is to continue to raise interest -menerus employers to improve the skills and knowledge possessed by raising awareness and training.